Implantación del sistema contable en la Farmacia Sucre I, provincia del Guayas, cantón El Triunfo, periodo enero -marzo del 2014 - Valle Arévalo, Maribel del Carmen (2015)
The present thesis work entitled "implementation of the accounting in the pharmacy system SUCRE I, province of GUAYAS, EL TRIUNFO CANTON, period January - March 2014", it was complying with the regulations of the University national of Loja, prior to the award of the title of engineer in accounting and CPA auditing, In addition to contribute with knowledge and applying them to this business unit you need to organize your financial information by the accounting records, as set out in the international accounting standards, law on service of internal revenue, trade code; and timely information. Given the compliance to the objectives with the implementation of the accounting system, began with the development of the Plan and Manual of accounts according to the needs of the pharmacy, developed the accounting process starting with the lifting of the initial inventory, allowing you to know the property, rights and obligations of the business; These consolidated data facilitated to carry out the State of initial situation is met where the assets, liabilities and assets; subsequently occurred in the book daily transactions for the period of study, internal documents were made and at the end the financial statements were obtained. Conclusion at the end of the implementation of the system of permanent inventory accounting determined usefulness in the study period; result that became known to the owner of the business; Therefore it is recommended to continue the implementation of the commercial accounting since it will provide reasonable, reliable and timely information to its owner for a successful decision making process when the case warrants it